STRATEGI DAKWAH ABU BAKAR ASH-SHIDDIQ - Bimby, Patmawati, Habibi (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2023)
ABSTRACT The purpose of this study was to reveal Abu Bakar Ash-Shiddiq's Da'wah Strategy: (1) Da'wah Bi al-Lisan Abu Bakar Ash-Shiddiq; 2) Da'wah Bi al-hal Abu Bakar Ash-Shiddiq; 3) Da'wah Bi al-yad Abu Bakar Ash- Shiddiq: 4) Da'wah Bi al-tadwin Abu Bakar Ash-Shiddiq; 5) Da'wah Uswah Hasanah Abu Bakar Ash-Shiddiq. This research includes qualitative research. The data sources of this research consist of Primary sources and Secondary sources. Primary data of this research was a source of literature on reading in the form of books related to the concept of preaching Abu Bakar Ash-Shiddiq.The secondary data sources of this research include written sources. Written data sources are data sources in the form of books. The data sources that researchers obtain were sourced from journals, and other books. Based on the analysis conducted, the researchers concluded that: 1) In using the Bi al-Lisan missionary strategy, Abu Bakar Ash-Shiddiq succeeded in converting several friends who later became important figures in Islamic history, including Uthman bin Affan, Abdurrahman bin Auf , Zubair bin Awwam, Sa'ad bin Abi Waqas. 2) On the preaching of Bi Al-Hal Abu Bakar Ash-Shiddiq managed to establish government departments to help carry out his power, including: The state treasurer managed by Abu Ubaidah, the executive branch of Ali bin Abi Talib, Ustsman bin Affan, and Zaid bin Thabit as secretary, judiciary institutions by Umar bin Khattab, and state defense/security including several commanders in chief at the time, namely: Khalid bin Walid, Musanna bin Harisah, Amr bin 'Ash, and Zaid bin Sufyan. 3) In Da'wah Bi Al-Yad, Abu Bakar Ash-Shiddiq succeeded in fighting people who were reluctant to pay zakat, apostates, and expansion of territory into Syria and Iraq. 4) On the preaching of Bi al-Tadwin Abu Bakar Ash-Shiddiq managed to collect the Koran during his reign. 5) In the missionary strategy of Uswah Hasanah Abu Bakar Ash-Shiddiq he was a good role model, he was a friend who has a high level of faith, even the Prophet Muhammad. Gave him the title Ash-Shiddiq which means 'speaking the truth'. Abu Bakar is a leader who has a charismatic spirit even though he was a leader but he really applied the attitude of Tawadhu', his appearance was very simple and he was a very generous person. Keywords: Abu Bakar Ash-Shiddiq, Strategy, Da'wah